Children's experiences and perceptions of poverty in Ethiopia - Tafere, Y (Young Lives, 2012)
This paper presents children’s experiences and perceptions of poverty. It draws on survey and qualitative data from the Young Lives study of poor children in Ethiopia. Through group exercises, discussions and interviews, children and young people aged 13-17 collectively and individually provided their perceptions of the causes, indicators and consequences of poverty in their communities. They felt that they were more victims of the consequences of poverty while they rarely contributed to its causes. Their poverty experiences suggest the multidimensional, contextualised and intergenerational nature of child poverty. The children and young people have also demonstrated their agency and resilience by providing their lived accounts and suggestions for tackling poverty and by practically contributing to family incomes. They identified what they believed to be the root causes of poverty and suggested what the Government, parents and children should do to reduce it. For example, they thought that child poverty could be addressed by changing some of the societal values that contribute to its perpetuation. The paper argues that children’s lived experiences of poverty place them in an optimum position to provide us with strong evidence to advance our knowledge of childhood poverty and develop apt policies to reduce it. Through this argument, this paper aims to provide both theoretical and practical contributions.